Comparing the environmental efficiency of milk and beef production through life cycle assessment of interconnected cattle systems. (20th December 2020) - Mazzetto, Andre M.; Bishop, George; Styles, David; Arndt, Claudia; Brook, Robert; Chadwick, Dave
Abstract: Dairy production has a substantial environmental impact. Currently, most studies analysing the environmental burdens of milk production employ attributional Life Cycle Assessment (LCA), for cradle to farm-gate analysis of dairy systems. This approach calculates environmental footprints per kg fat and protein corrected milk (FPCM). However, milk and beef production are inherently interconnected, and a narrow focus on milk production neglects wider synergies and trade-offs across cattle systems, outside dairy farm boundaries. For the first time, we applied an expanded boundary LCA of coupled dairy and beef production in Latin America, considering 1 kg FPCM plus 100 g of beef as functional unit (FU) to reflect the current global beef:milk demand ratio and taking into account the complexities of Costa Rican cattle production systems. Boundaries encompassed fattening of surplus dairy calves and incurred or avoided suckler-beef production needed to deliver the FU. A database of 552 Costa Rican farms (203 beef and 349 dairy farms) was analysed using a farm LCA model to generate results across five impact categories (Global Warming Potential – GWP; Eutrophication; Acidification; Abiotic Resource Depletion; and Land Occupation - LO). Normalised scores indicated that cattle systems contribute most strongly to per capita GWP and LO burdens. Cradle to farm-gate attributional LCA showed that milk produced by dual-purpose farms had the largest GWP and LO footprints, whilst specialist farms had the smallest footprints, per kg FPCM. The expanded boundary LCA showed that dual-purpose farms generated smaller GWP footprints per kg FPCM plus 100 g beef than specialised dairy farms, though still required more land. Key factors were the herd structure, influencing the amount of beef produced, and milk yields per animal, reflecting the level of dairy specialisation. This new evidence on the environmental efficiency of cattle production systems emphasises the imperative to consider both milk and beef production as well as multiple environmental pressures across interconnected milk and beef production systems when designing sustainable intensification mitigation strategies. Highlights: Applying a milk-plus-beef functional unit better represents dairy system multifunctionality. Including downstream fattening of dairy calves captures wider cattle system efficiency. Specialised dairy farms exhibited the smallest carbon and land footprints per kg milk. Dual-purpose dairy-beef farms exhibited smallest footprints for milk-plus-beef production.